Proposing a Method for Splicing Steel Columns to Improve Force Path and Facilitate Construction - Sh. Mahdlooyi; A.R. Ghiami Azad; S.R. Mirghaderi (مهندسی عمران شریف, 2023)
Current methods of splicing columns with different depth sizes have a long total load path as well as large and expensive details. These details are sometimes overly complicated and hard to fabricate. To shorten the load path and make fabrication easier and more economical, a middle plate is proposed in this study to be placed between the two columns to connect them. The plate is butt-welded to both the lower and the upper portions of the column. Although this type of splice has been used occasionally in steel structures, its behavior is mainly unknown and research and code specifications regarding this type of splice are very limited. The current research studied the overall behavior of columns connected by this type of splice and obtained the minimum plate thickness required for typical columns to meet codes provisions. To provide the possibility of filling potential hollow sections with concrete, it is recommended to use a hallow plate in box-shaped columns. This study conducted finite element analysis on box- and H-shaped columns with different upper column depths. The influence of the plate thickness and shape on the strength and stiffness of splice in each combination was studied and minimum plate thickness was obtained. The splice exhibited satisfactory strength and stiffness in regular combinations. In combination with an upper column depth reduction of less than 5cm in box-shaped profiles and less than 7.5cm in the H-shaped profiles, the splice plate with a thickness of 5cm or more meets the criteria for both strength and stiffness. Decreasing the upper column depth increases the demand on the splice plate and a thicker plate is needed. Moreover, the shape of the splice plate, i.e., hollow plate or regular plate, had a large impact on the column behavior as the required thickness was greater in hollow plates. Results of stiffness analysis showed that decreasing the upper column depth and overall height of the column decreases the axial stiffness of the column.